Soil degradation in sub-Saharan Africa and crop production options for soil rehabilitation - Zingore, Shamie; Mutegi, James; Agesa, Beverly; Tamene, Lulseged D.; Kihara, Job Maguta (International Plant Nutrition Institute, 2015)
Soil degradation associated with poor soil fertility management practices is a major factor underlying poor agricultural productivity in sub-Saharan Africa. About 65% of the agricultural land is degraded, mainly due to low nutrient application, soil erosion and soil acidification. Increased fertilizer use and balanced nutrient management in combination with various organic matter inputs offer the best prospects to reverse soil degradation.